Phenolic Compounds in Apple (Malus x domestica Borkh.): Compounds Characterization and Stability during Postharvest and after Processing - Alessandra Francini; Luca Sebastiani (Antioxidants, 2013)
This paper summarizes the information on the occurrence of phenolic compounds in apple (Malus x domestica Borkh.) fruit and juice, with special reference to their health related properties. As phytochemical molecules belonging to polyphenols are numerous, we will focus on the main apples phenolic compounds with special reference to changes induced by apple cultivar, breeding approaches, fruit postharvest and transformation into juice.